2017
DOI: 10.3390/catal7100286
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Cyclic Chemical Looping Steam Methane Reforming over Yttrium Promoted Ni/SBA-16 Oxygen Carrier

Abstract: Abstract:In this work, the modification of Ni/SBA-16 oxygen carrier (OC) with yttrium promoter is investigated. The yttrium promoted Ni-based oxygen carrier was synthesized via co-impregnation method and applied in chemical looping steam methane reforming (CL-SMR) process, which is used for the production of clean energy carrier. The reaction temperature (500-750 • C), Y loading (2.5-7.4 wt. %), steam/carbon molar ratio (1-5), Ni loading (10-30 wt. %) and life time of OCs over 16 cycles at 650 • C were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…It was reported that doping with Y 3+ improved the rate of carbon removal due to oxygen vacancies, which persuaded oxygen radicals from CO 2 to react with coke. [35,39,53,62,63] Thus, a possible removal of carbon could have taken place according to the reverse Boudouard reaction (CO 2 + C = 2CO). [53] The latter may be also linked with possible re-dispersion of the Ni particles (described further in the text).…”
mentioning
confidence: 99%
“…It was reported that doping with Y 3+ improved the rate of carbon removal due to oxygen vacancies, which persuaded oxygen radicals from CO 2 to react with coke. [35,39,53,62,63] Thus, a possible removal of carbon could have taken place according to the reverse Boudouard reaction (CO 2 + C = 2CO). [53] The latter may be also linked with possible re-dispersion of the Ni particles (described further in the text).…”
mentioning
confidence: 99%
“…It is applied widely on large-scale industrial processes due to the low cost, easy accessibility and environmental-friendly nature [15]. It is normally used to maximize the average methane conversion and hydrogen production yield by employing nickel based oxygen carrier catalysts [16]. The temperature range of such process is between 500 and 750 • C [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is normally used to maximize the average methane conversion and hydrogen production yield by employing nickel based oxygen carrier catalysts [16]. The temperature range of such process is between 500 and 750 • C [16]. Sorption enhanced reduction of the nickel oxygen carrier catalyst is used in chemical looping, aiming to capture CO 2 during conventional steam reforming [17].…”
Section: Introductionmentioning
confidence: 99%
“…[18]), H 2 evolution [25], and CO 2 reduction [26,27]. Six other papers focus on conventional catalysis ("dark" reactions), reporting efficient H 2 production [28,29], synthesis of ethanol and butanol [30], direct conversion of CO 2 and methanol to dimethyl carbonate [31], water purification [32], and advanced characterization of catalysts by X-ray absorption fine structure (EXAFS) spectroscopy [33]. The majority of studies have been performed with particulate catalysts (nanoparticles (NPs)), but organized nanostructures, such as nanotubes (TiO 2 /Cu x O y [18], carbon nanotubes (CNTs) [30,32]) and nanowires (CeO 2 [31]) have also been used.…”
mentioning
confidence: 99%
“…The Fe 2 O 3 -MgAl 2 O 4 with narrowed mesopore-sized (2.3 nm) was successfully synthesized as an ultra-pure lattice oxygen transport medium. Furthermore, Daneshmand-Jahromi et al analyzed the role of yttrium promoted Ni/SBA-16 as an oxygen carrier in steam methane reforming [29]. The reaction temperature, Y and Ni loading, steam/carbon molar ration, and lifetime of the oxygen carrier were investigated.…”
mentioning
confidence: 99%